2018
DOI: 10.21278/brod69201
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Investment in Renewable Energy Systems for Shipyards

Abstract: SummaryShipbuilding industry is generally considered as one of the key global industries. It consumes a significant amount of energy and leaves a strong footprint on the environment. It is therefore required to try to increase renewable energy sources in the shipbuilding industry in accordance with the adopted international legislation. This will improve energy efficiency of shipyards and reduce their impact on the environment. The present preliminary study contributes to those goals as application of sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Technological innovations should be cost effective for an energy efficiency of main engine and a sustainable improvement (Xie et al [20]). Solar panels are considered as the most suitable and sustainable technology (Hadžić et al [21]). Gaining wood durability, adopting alternative native wood or wood cored sandwich composites may be a solution to enhance the artisanal boatyard's sustainability (Walter et al [22]).…”
Section: Analyses Of the Resultsmentioning
confidence: 99%
“…Technological innovations should be cost effective for an energy efficiency of main engine and a sustainable improvement (Xie et al [20]). Solar panels are considered as the most suitable and sustainable technology (Hadžić et al [21]). Gaining wood durability, adopting alternative native wood or wood cored sandwich composites may be a solution to enhance the artisanal boatyard's sustainability (Walter et al [22]).…”
Section: Analyses Of the Resultsmentioning
confidence: 99%
“…In addition, the development of smart shipyards using data envelopment analysis has been shown by Woo et al 46 and the implementation of Industry 4.0 at shipyards using fuzzy AHP-TOPSIS hybrid method has been explained by Cil et al 47 The utilization of different types of renewable energy in shipyards has been investigated in various studies. Hadži c et al 48 identified the feasibility of investments in renewable energy systems for shipyards and the use of a photovoltaic power plant for a shipyard, and the potential of wave power parks for shipyards in Portugal was explored by Miglietta 49 and Neumann et al, 50 respectively. At the same time, the implementation of floating offshore wind platforms in shipyards was addressed by Castro-Santos et al 51,52 Energy efficiency decisions and the selection of main engines in a sustainable shipyard supply chain were addressed by Xie et al 53 and Krishnan et al 54 examined optimal cargo handling in a shipyard.…”
Section: Of Operational Co 2 Emissionsmentioning
confidence: 99%
“…The human element (such as Training, 126 Governance and Corporate Social Responsibility, 127 Education, 128 Capacity building, 129 Awareness Raising, 130 Research and Development (R&D) 131 ) was chosen as one of the disciplines in the EnMF because within the complex socio-technical system and shipyard sectors plays a crucial role and is continually being transformed and redefined by technological advancement. 132 Moreover, technology and innovation (including Digitalization (fourth Industrial revolution), 133,134 Micro Grid, 135 Renewable Energy, 48 Electrification (Battery, Fuel cell etc. ), 136 Alternative clean fossil fuel (Natural gas etc.…”
Section: Concept Of Enmfmentioning
confidence: 99%
See 1 more Smart Citation
“…Smart & micro grid [30] Digitalization (4th Industrial revolution) [31,32] Renewable energy [33,34] Electrification (Battery, Fuel cell) [35] Carbon Capture and Storage (CCS).…”
Section: Human Factorsmentioning
confidence: 99%